Pore-throat structure characterization of carbon fiber reinforced resin matrix composites: Employing Micro-CT and Avizo technique. - Yong Li (Public Library of Science (PLoS), 2021)
Micro-CT technique poses significant applications in characterizing the microstructure of materials. Based on the CT three-dimensional(3D) reconstruction technology and "Avizo" 3D visualization software, the microscopic pore-throat structure of porous media can be quantitatively characterized. This paper takes the carbon fiber reinforced resin matrix composites as an example to introduce the operation process of "Avizo" in details, which mainly covers the following modules: Volume Edit, Interactive Thresholding, Fill Holes, Mask, Separate Objects and Generate Pore Network Model, then further discuss the difficult problems when the "Avizo" is employed to analyze. The microstructures of carbon fiber reinforced resin matrix composites illustrate that pores in the upper part of sample are dramatically dispersed, and mainly concentrated in the lower part of sample. The porosity of adopted cuboid is 3.6%, accordingly the numbers of pores and throats reach 268 and 7, respectively. The equivalent radius of pores seems mainly distributed in the range of 0.7-0.8μm, accounting for 28.73% of the total pore number. The surface area of pore ranges from 5 to 10μm2, accounting for 14.16% of the total pore number. The pore volume concentrates in the range of 1-20μm3, accounting for 57.46% of the total pore number. In addition, the equivalent radius of throat mainly concentrates in the range of 1-5μm, the overall length of throat is distributed in the range of 37-60μm, and the equivalent area of throat is distributed non-uniformly in the range of 5-75μm2. This work provides a basis for the further investigation of fluid migration mechanism and law in the composite materials by the numerical simulation methodology.